Pelatihan Manajemen Emosional terhadap Perilaku Caring Perawat - IGAA Sherlyna Prihandhani; Made Oktaviani Bulan Trisna; Ni Kadek Ayu Trya Septi Getsuyobi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine emotional management training on nurses' caring behavior. This research method is a quantitative study with a quasi-experimental pre-test and post-test design using a control group. The results showed that the statistical tests using Mann Whitney obtained a p-value of 0.009. In conclusion, there is an effect of emotional management training on the caring behavior of nurses at Balimed Denpasar Hospital. Keywords: Emotional Management, Training, Nurse Caring Behavior